Developing progressive web applications : moving beyond the web/native distinction (O'Reilly Media, 2016)
"A progressive web app (PWA) is a new way to deliver an app-like experience to a mobile device. Instead of downloading an app from a store, the mobile's browser takes the user to the PWA's URL. Visit the URL often enough and the browser asks, 'Do you like this PWA?' If the user answers yes, the PWA will show up as an icon on the mobile's home screen. It's a paradigm shift for delivering Internet experiences that's safe to access, SEO discoverable, works online or offline, and shows up on any device. Mobile guru Max Firtman gives you entre to the new world of PWAs in this overview of what they are, how to spot them, how to make them, and why you should make them."--Resource description page.